设[img=107x52]1803026d4388ee9.png[/img],则[img=32x18]1803026d4a861cf.png[/img]为函数[img=32x25]1803026d52a5337.png[/img]的( ).
A: 可去奇点
B: 一阶极点
C: 二阶极点
D: 本性奇点
A: 可去奇点
B: 一阶极点
C: 二阶极点
D: 本性奇点
举一反三
- 设[img=107x52]18031c187453eaf.png[/img],则[img=32x18]18031c187cafd3f.png[/img]为函数[img=32x25]18031c1884b5243.png[/img]的( ). A: 可去奇点 B: 一阶极点 C: 二阶极点 D: 本性奇点
- 设[img=107x52]18036d3b5566374.png[/img],则[img=32x18]18036d3b5e8a99e.png[/img]为函数[img=32x25]18036d3b66c1424.png[/img]的( ). A: 可去奇点 B: 一阶极点 C: 二阶极点 D: 本性奇点
- 设[img=107x52]180382eff9305c5.png[/img],则[img=32x18]180382f0016ba0b.png[/img]为函数[img=32x25]180382f008fa906.png[/img]的( ). A: 可去奇点 B: 一阶极点 C: 二阶极点 D: 本性奇点
- 设[img=104x42]17e4408b42cf9f3.png[/img],则[img=37x19]17e437bb6ca1ad0.png[/img]是函数的( ) A: 可去奇点 B: 一阶极点 C: 二阶极点 D: 解析点
- 设[img=104x42]17e0b2f0da99946.png[/img],则[img=37x19]17e0b2f0e4d2f9e.png[/img]是函数的( ) A: 可去奇点 B: 一阶极点 C: 二阶极点 D: 解析点